2012
DOI: 10.1007/s13187-012-0343-2
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Distress on Knowledge Transfer for Men Newly Diagnosed with Prostate Cancer

Abstract: The purpose of this inquiry was to evaluate the efficacy of prostate cancer education sessions. Implementation of 3-h patient educational sessions was intended to provide men newly diagnosed with localized prostate cancer, who face difficult and complex decisions, information about potential treatment options. Fifty-seven men completed the distress thermometer assessment before the education session to assess baseline levels of distress. Seven of the men were interviewed post-educational session to determine t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 36 publications
0
10
0
Order By: Relevance
“…Patients and families want to be provided the opportunity to be respected partners in their care and meaningfully involved in decision making about their health. 6 The value of PCC More recently, PCC has been emphasized within trends that focus on meeting the health care needs of specific patient populations. PCC is considered to be at the core of cultural competency 7 and foundational to humanistic care delivery to people experiencing socioeconomic disadvantage.…”
Section: Some Pcc Historymentioning
confidence: 99%
See 1 more Smart Citation
“…Patients and families want to be provided the opportunity to be respected partners in their care and meaningfully involved in decision making about their health. 6 The value of PCC More recently, PCC has been emphasized within trends that focus on meeting the health care needs of specific patient populations. PCC is considered to be at the core of cultural competency 7 and foundational to humanistic care delivery to people experiencing socioeconomic disadvantage.…”
Section: Some Pcc Historymentioning
confidence: 99%
“…Authentic PCC means that the patient's voice is heard loudly and clearly, not as an adjunct to a professional initiative, but as a knowledgeable other and partner with experiences capable of informing health care practices. 6 When care is provided within a collaborative approach, the knowledge that guides treatment or prevention emerges in a space shared and actively negotiated by both parties. In other words, true PCC does not belong to either the health care provider or to the patient/family.…”
Section: On Defining Pccmentioning
confidence: 99%
“…However, given evidence that many men and their families experience prostate cancer treatment decision making as challenging, 2123 we predicted that greater engagement in the process, indicated by higher decisional control and knowledge, would be associated with greater decision-making difficulty. It is possible that knowledge has a larger impact on treatment decision making to the extent that patients are actively involved in the treatment decision-making process.…”
mentioning
confidence: 99%
“…As noted previously, in the oncology context, patients are traditionally approached for cancer clinical trials when they are newly diagnosed or have been found to have worsening of their disease, when levels of distress are high. Higher levels of psychological distress can interfere with knowledge uptake (26), and distress has also been associated with higher levels of decisional conflict (2728). Moreover, psychological distress has been associated with greater perceived barriers to enrollment in clinical trials (9).…”
mentioning
confidence: 99%